2011
DOI: 10.1371/journal.pone.0027277
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Morphometric Vertebral Fractures by Artificial Neural Networks: Analysis from GISMO Lombardia Database

Abstract: BackgroundIt is known that bone mineral density (BMD) predicts the fracture's risk only partially and the severity and number of vertebral fractures are predictive of subsequent osteoporotic fractures (OF). Spinal deformity index (SDI) integrates the severity and number of morphometric vertebral fractures. Nowadays, there is interest in developing algorithms that use traditional statistics for predicting OF. Some studies suggest their poor sensitivity. Artificial Neural Networks (ANNs) could represent an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…In a study on about 370 Italian postmenopausal women the mean daily calcium intake was about 600 mg/day and the 20% of subjects were taking less than 300 mg/day of calcium from dairy products (22). In keeping, in a more recent study in a population of Italian patients with type 1 diabetes the 50% of men and 27% of women showed a calcium intake below the threshold recommended for the Italian general population (23).…”
Section: Calcium Intakementioning
confidence: 94%
“…In a study on about 370 Italian postmenopausal women the mean daily calcium intake was about 600 mg/day and the 20% of subjects were taking less than 300 mg/day of calcium from dairy products (22). In keeping, in a more recent study in a population of Italian patients with type 1 diabetes the 50% of men and 27% of women showed a calcium intake below the threshold recommended for the Italian general population (23).…”
Section: Calcium Intakementioning
confidence: 94%
“…According to the advantages of nonlinearity, fault tolerance, universality, and real-time operation, ANNs have been proposed as a quite suitable algorithm for modeling complex non-linear relationships in health care research (Baxt et al, 1995;Cross et al, 1995;Kung and Hwang, 1998). Eller-Vainicher et al (2011) identified the promising role of ANN in predicting osteoporotic fracture among postmenopause osteoporosis women. For the comparison of the characteristics between ANNs and logistic regression applied to this epidemiological research field, a study has established prediction models for predicting living setting after hip fracture by ANNs and logistic regression, and shown that ANN is slightly better than logistic regression (Ottenbacher et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing approaches have used an SVM classifier with an RBF-kernel [33][34][35] or multi-layer perceptron (MLP)-based ANN classifier models [36][37][38][39] to distinguish osteoporotic patients from normal individuals. Therefore, the classification performance of the proposed approach was compared to that of an SVM classifier with various kernels.…”
Section: Discussionmentioning
confidence: 99%